Nutrient comparisons among the noble scallops Chlamys nobilis with three different shell colours to provide advices for consumers to choose high-quality food - He, Cheng; Ye, Ting; Zeng, Junxi; Zhang, Hongkuan; Sun, Yizhou; Zhang, Chuanxu; He, Xianqing; Qiu, Jiale; Zheng, Huaiping (Frontiers in Marine Science, 2024)
Introduction In aquatic animals, colors not only reflect their sensory qualities but also affect their nutritional components and market price. Noble scallop Chlamys nobilis is an importantly economical bivalve cultured in the south sea of China and renowned for its various shell colors. Methods In this study, the nutrient compositions were compared among golden, yellow, and brown shell colour noble scallops originating from the same population for breeding new varieties. Results Among three colour scallops, there is no significant difference in the content of moisture, ash, and total protein content (TPC) but significant differences in total carotenoid content (TCC), total lipid content (TLC), and amino acids (AAs) (P < 0.05), with the TCC of the brown scallop being about 2 times lower. The yellow scallop contained the same nutrients as TCC, TLC, ∑PUFAs (including EPA and DHA), and n-3/n-6 as the golden scallop, and both were significantly higher than the brown scallop (P < 0.05), but they had significantly lower ∑SFAs than the latter (P < 0.05). The correlation between the nutrient indices and the shell color of scallops was 67.5%. There is a significantly positive correlation between TCC and ∑PUFAs (P < 0.05), while a significantly negative correlation exists between TCC and ∑SFAs (P < 0.05). More importantly, the yellow scallop had significantly higher EAAs and FAAs than the golden scallop (P < 0.05). Discussion This study showed that the yellow noble scallop not only enriched in carotenoids and PUFAs but also enriched in amino acids. Therefore, the yellow scallop is more benefit to human health, which can provide high-quality food for customers.